Exonuclease and Nicking Endonuclease‐Assisted Amplified Electrochemical Detection of Coralyne. Issue 8 (23rd May 2017) - Wang, Jue; Yu, Jing; Zhou, Xiaoyu; Miao, Peng
Abstract: Based on the catalysis of exonuclease I (Exo I) and nicking endonuclease (NEase), a novel electrochemical biosensor for the detection of coralyne is fabricated in this work. Specifically, DNA probe 1 can be protected from Exo I‐catalyzed digestion upon interacting with coralyne, the most representative homo‐adenine binding molecule. Subsequently, DNA probe 1 can further hybridize with a pendant sequence on top of the DNA tetrahedron, which is previously modified on the gold electrode surface. As the formed duplex contains the recognition site of Nb.BssSI, a type of NEase, the pendant sequence is thus cleaved, releasing the electrochemical probe on the 5'‐terminus from the electrode surface. DNA probe 1 is also released, which could then initiate the subsequent cycles of NEase‐catalyzed cleavage and amplify the declined electrochemical signals. We can determine coralyne in a linear range from 0.1 to 100 nM with the detection limit of 0.07 nM by using the proposed method. Experiments in real samples also demonstrate good results, showing excellent practical utility of this method. Moreover, it could be extended to assay other analytes by modifying certain DNA sequences. Abstract : Exonuclease and endonuclease : Based on the catalysis of exonuclease and nicking endonuclease, a novel electrochemical biosensor for the detection of coralyne is fabricated. Coralyne can be determined in a linear range from 0.1 to 100 nM with a detection limit of 0.07 nM (see picture).